Sustainability: extending the virtue of personal data legislation to goods and products - Philippe, Eva (Vilnius University Open Series, 2020)
This contribution addresses the notion of sustainability and its modalities as an element of public order enabling the European Union to regain its technological sovereignty through the emergence of a possible new environmental measure. Constraining the manufacturers, this measure is compliant with the free markets requirements. Only the intellectual property rights may constitute a real obstacle to its application.